High resolution analysis of GeH4 in the dyad region: Ro-vibration energy structure of 70GeH4 and line strengths of MGeH4 (M = 70, 72, 73, 74, 76). (October 2019) - Ulenikov, O.N.; Gromova, O.V.; Bekhtereva, E.S.; Raspopova, N.I.; Kuznetsov, A.V.; Sydow, C.; Bauerecker, S.
Highlights: High resolution analysis of the v2/v4 bands of M GeH 4 ( M = 70, 72, 73, 74, 76 ) . Resonance interactions in spherical top molecules. Determination of spectroscopic parameters. Analysis of line strengths. Abstract: The infrared spectrum of M GeH4 ( M = 70, 72, 73, 74, 76 ) was measured at the temperature of (294.5 ± 0.3) K in the 740-960 cm − 1 region with a Bruker Fourier transform infrared spectrometer IFS125 and analyzed. The line positions of the ν 2 / ν 4 bands and the ro-vibrational energy structure of corresponding upper vibrational states of 70 GeH4 were analyzed. The strengths of 1079 experimentally recorded spectral lines (243/270/152/262/152 lines for the isotopologues 70 GeH4 / 72 GeH4 / 73 GeH4 / 74 GeH4 / 76 GeH4 ) with the value of quantum number J max = 19 were determined from the fit of their line shapes with a Hartmann–Tran line profile and were used then in the weighted fit for determination of the effective dipole moment parameters of the ν 4 band. The obtained sets of parameters reproduce the initial experimental line intensities with the d rms = 3.46 / 3.12 / 3.21 / 3.38 / 3.45 / % for the 70 GeH4 / 72 GeH4 / 73 GeH4 / 74 GeH4 / 76 GeH4 species, respectively. A list of transitions with their line intensities is generated in the HITRAN format up to the value of quantum number J = 40 .